2021
DOI: 10.3390/min11010081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Entrainment on Cemented Mine Backfill Properties: Analysis Based on Response Surface Methodology

Abstract: As part of an extensive research program exploring the potential benefits of using air-entraining admixtures in mine backfill, the experimental study presented in this paper investigates the effect of cement and entrained air dosages on mine backfill unconfined compressive strength (UCS), fresh density, and dry density. Backfill specimens were prepared using silica sand, normal Portland cement, water, and an entrained air admixture. An experimental design with response surface methodology was adopted to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…After removing each hardened sample from the cylindrical mold by injecting air pressure into the predrilled hole at the bottom of the mold [75] and finishing both surfaces using a surface grinder equipment to achieve a flat area, the height and diameter of samples were measured carefully in terms of maintaining a height-to-diameter ratio within 2 to 2.5 according to ASTM D2166 [76]. All of that comes before conducting the UCS test, which was successfully performed by Unitronic Compression (model S205-05M) made by MATEST Co., Italy, which has a load capacity of up to 50 kN (Figure 5).…”
Section: Uniaxial Compressive Strength (Ucs) Testmentioning
confidence: 99%
“…After removing each hardened sample from the cylindrical mold by injecting air pressure into the predrilled hole at the bottom of the mold [75] and finishing both surfaces using a surface grinder equipment to achieve a flat area, the height and diameter of samples were measured carefully in terms of maintaining a height-to-diameter ratio within 2 to 2.5 according to ASTM D2166 [76]. All of that comes before conducting the UCS test, which was successfully performed by Unitronic Compression (model S205-05M) made by MATEST Co., Italy, which has a load capacity of up to 50 kN (Figure 5).…”
Section: Uniaxial Compressive Strength (Ucs) Testmentioning
confidence: 99%
“…Several works (e.g. Dai et al, 2019;Sun et al, 2020;Hefni and Hassani, 2021) have been done on CPB materials through the RSM technique. Nevertheless, none of them mentions the effect of silicate modulus, slag fineness and activator concentration on 3-and 28 day UCS of AAS-CPB.…”
Section: Introductionmentioning
confidence: 99%
“…The development system applied in mineral extraction was analyzed, and a method of selecting deposit development technology and reasonable filling mixture composition under given filling parameters was proposed. Saudi Arabian scholars [22,23] studied the effects of cement and air-entraining doses on the strength, fresh density, and dry density of mine backfilling materials through a uniaxial compressive strength test. The research results showed that the air-entraining admixture can effectively improve the strength of the backfilling material and improve its filling fluidity.…”
Section: Introductionmentioning
confidence: 99%